Dame Nellie Melba - Melba, Nellie, Dame, 1861-1931 (1925)
Photographs taken from her book "Melodies and memories" showing her performing in various operas.
Keywords: Melba, Nellie, -- Dame, -- 1861-1931 -- Portraits; Singers -- Australia -- Portraits; Opera -- Australia -- History; Women singers -- Australia -- Portraits